2023
DOI: 10.3389/fnagi.2023.1134472
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of selegiline for the treatment of Parkinson's disease: A systematic review and meta-analysis

Abstract: BackgroundDrug efficacy generally varies with different durations. There is no systematic review analyzing the effect of selegiline for Parkinson's disease (PD) on different treatment duration. This study aims to analyze how the efficacy and safety of selegiline changes for PD over time.MethodsPubMed, the Cochrane Library, Embase, China National Knowledge Infrastructure and Wanfang Database were systematically retrieved for randomized controlled trials (RCTs) and observational studies of selegiline for PD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Selegiline was also effective in improving depressive symptoms in PD in a recent meta-analysis [ 52 ]. A systematic review showed that safinamide, a selective reversible MAO-B inhibitor and modulator of voltage-sensitive calcium and sodium channels that also affect glutamatergic neurotransmission, may also be beneficial for depression in PD [ 53 ].…”
Section: Pharmacological Treatment Approaches For Depression In Pdmentioning
confidence: 99%
“…Selegiline was also effective in improving depressive symptoms in PD in a recent meta-analysis [ 52 ]. A systematic review showed that safinamide, a selective reversible MAO-B inhibitor and modulator of voltage-sensitive calcium and sodium channels that also affect glutamatergic neurotransmission, may also be beneficial for depression in PD [ 53 ].…”
Section: Pharmacological Treatment Approaches For Depression In Pdmentioning
confidence: 99%
“…In this context, selegiline appears to have benefits in improving PD symptoms but has a high risk of adverse events, especially neuropsychiatric issues. Further studies are needed to better understand this correlation and assess the long-term efficacy and safety of selegiline [176].…”
Section: Pharmacological Modulation Of Hsps and Neuroprotective Effec...mentioning
confidence: 99%
“…Its primary mechanism of action involves the inhibition of monoamine oxidase (MAO) impeding the process of reuptake of monoamine neurotransmitters inside the central nervous system, leading to an increase in the quantities of physiologically active monoamines present at the synaptic cleft. 18,19 Selegiline is additionally utilized off-label for the manage-ment of attention-deficit hyperactivity disorder. 20 One of the byproducts of the MAO-catalyzed amine oxidation reaction is hydrogen peroxide, which can be further processed into reactive oxygen species to cause cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%